Nierenersatzverfahren: Information, Aufklärung, Dokumentation - Galle, Jan; Reitlinger, Jana (DMW - Deutsche Medizinische Wochenschrift, 2018)
In renal replacement therapy, different methods are available: hemodialysis (HD), peritoneal dialysis (PD), and kidney transplantation (KTx). In addition, variants can be used: HD as a home HD or center HD, PD as a conventional PD or automated (cycler) PD, KTx as a potentially short-term predictable living donation or conventional donor kidney donation. The patient and his familiar or caring environment must be informed accordingly. This means first of all: information about which procedures of kidney replacement therapy are possible and can be offered. Then the specific risks associated with each procedure should be elucidated (e. g. HD and shunt bleeding, PD and peritonitis, KTx and infections/neoplasias). This necessarily includes a structured documentation of the educating center/doctor about the communicated information and decisions taken.
Keywords: Dialyse; spezielle Risiken; Aufklärung; Dokumentation